2016
DOI: 10.1159/000445036
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Galla chinensis </i></b>Compounds Remineralize Enamel Caries Lesions in a Rat Model

Abstract: Objectives: To investigate the effect of Galla chinensis chemical compounds on enamel caries remineralization in rats. Methods: A total of 40 rats were inoculated with Streptococcus sobrinus 6715 and fed a cariogenic diet (Keyes 2000). The rats were randomly divided into 4 groups and treated topically twice a day with each of the following extracts (or control) for 5 weeks: distilled and deionized water (DDW, negative control); 1,000 ppm NaF (positive control); 4,000 ppm G. chinensis crude aqueous extract (GCE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 38 publications
1
21
0
2
Order By: Relevance
“…Figure 7 shows TEM and SAED analyses of mineral phases formed during spontaneous mineralization experiments in the absence and presence of peptide (50 μg/mL). Mineral phase identification was based on the broad diffuse SAED ring pattern ( Figure 7A , 15 min, insets) and the morphology of TEM observations ( Figure 7A , 15 min), which exhibited spherical shapes that are consistent with the known morphology of ACP ( Eanes, 2001 ; Zhang et al, 2016 ), similarly reported in other studies ( Mahamid et al, 2008 ). Then, a rapid decrease in pH was observed from 7.2 to 6.5, in correspondence to the formation of plate-like particles.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Figure 7 shows TEM and SAED analyses of mineral phases formed during spontaneous mineralization experiments in the absence and presence of peptide (50 μg/mL). Mineral phase identification was based on the broad diffuse SAED ring pattern ( Figure 7A , 15 min, insets) and the morphology of TEM observations ( Figure 7A , 15 min), which exhibited spherical shapes that are consistent with the known morphology of ACP ( Eanes, 2001 ; Zhang et al, 2016 ), similarly reported in other studies ( Mahamid et al, 2008 ). Then, a rapid decrease in pH was observed from 7.2 to 6.5, in correspondence to the formation of plate-like particles.…”
Section: Resultssupporting
confidence: 81%
“…After the remineralization treatment, the mineral density and profiles of each specimen were determined with an Inveon micro-CT system (Siemens AG, Germany). The micro-CT X-ray source was set at an operating voltage of 80 kV and 500 μA, providing a 10-μm isotropic voxel resolution ( Zhang et al, 2016 ). A mineral density calibration curve was generated by scanning three hydroxyapatite disks (50, 250, and 750 mg/mL) as reference phantoms ( Songsiripradubboon et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…These results could explain the GCE formed of different polyphenol compounds, which might slow down the remineralization of dentin surface by time, and offer more channels for ion transferring through the surface layer to the lesion body. 39…”
Section: Discussionmentioning
confidence: 99%
“…121 Ayrıca flor ve nanohidroksi apatit içeren remineralizasyon ajanları ile birlikte kullanımı değerlendirilmiş ve sinerjistik etkiye sahip olduğu gösterilmiştir. 122 Klinik kullanıma uyarlanabilmesi için toksikoloji testlerini de içeren ileri çalışmalara ihtiyaç vardır.…”
Section: Galla Chinensisunclassified